Analisis Pengaruh Service Quality, Product Quality Dan Price Terhadap Keputusan Pembelian Pada Lazarus Batik Jember - Ashilah, Khittah Ashilah Khittah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to examine and analyze: (1) The effect of service quality on purchasing decisions at Lazarus Batik Jember. (2) The effect of product quality on purchasing decisions at Lazarus Batik Jember. (3) The effect of price on purchasing decisions at Lazarus Batik Jember. This research is a quantitative study with a descriptive approach that was carried out at the Lazarus Batik Jember Boutique in September-October 2021. The population in this study were all consumers of Lazarus Batik Jember and had purchased fashion products from Lazarus Batik Jember. The sample in this study were 100 respondents and were taken using accidental sampling technique. Data were collected using a questionnaire and data analysis using multiple linear regression. The results of data analysis show that: (1) Service quality has a significant and significant effect on purchasing decisions at Lazarus Batik Jember; (2) The product quality has a significant and significant effect on purchasing decisions at Lazarus Batik Jember; (3) Price has a significant and significant effect on purchasing decisions at Lazarus Batik Jember; and (4) the quality of service, product, and price together have a significant and significant effect on purchasing decisions at Lazarus Batik Jember.